strategic management principles and practice
Global examples, multiple perspectives and dynamic presentation make this important new textbook the complete introduction for modern strategy courses. Encouraging students to be conscious of the perspectives, context and complexity that produce ideas about strategy, the experienced author team situate learning within a diverse range of environments to reflect the globalized and turbulent nature of today's business. Key Debates situated in every chapter provide a balanced introduction and highlight the subject's vibrancy by asking the student to tackle vital strategic questions such as: Are the five forces still relevant for today? Do boards control their executives? Should strategy be stable over time, or should it be changing? And is related better than unrelated diversification? Case Studies, Business Vignettes, Key Terms, Guided Further Reading and detailed Chapter References round out a comprehensive pedagogical framework while a complete supplements package ensures you can seamlessly integrate Witcher & Chau into your teaching for 2010 and beyond.
Includes index
Keywords: Strategy